Direct synthesis of cyanate anion from dinitrogen catalysed by molybdenum complexes bearing pincer-type ligand - Takayuki Itabashi; Kazuya Arashiba; Akihito Egi; Hiromasa Tanaka; Keita Sugiyama; Shun Suginome; Shogo Kuriyama; Kazunari Yoshizawa; Yoshiaki Nishibayashi (Nature Communications, 2022)
Direct conversion of dinitrogen to organonitrogen compounds is a challenging goal in nitrogen fixation chemistry. Here, the authors report the catalytic formation of cyanate anion from dinitrogen under ambient conditions using a molybdenum complex.